Pengembangan AI Generatif ChatBot berbasis Mobile App dengan MIT App Inventor - Suharto, Agus; Hartono, Rahmat (DPPM Universitas Pelita Bangsa, 2025)
This research explores the integration of generative artificial intelligence (AI) into mobile app development using MIT App Inventor, a visual programming platform widely adopted in educational settings. As generative AI technologies such as Large Language Models and image synthesis tools become more accessible, the potential for significantly enhancing creativity, personalization, and automation in mobile apps becomes clear. The research presents a prototype chatbot application with AI to a dynamic story generator built using Web App Inventor components to interact with external AI APIs. Through usability testing with high school students to evaluate technical feasibility, user experience, and pedagogical value, the research shows that generative AI can enrich learning outcomes and application functionality, although challenges remain in managing latency, API complexity, and ethical considerations. . The results of the study were evaluated using EUCS and Likert Scale as measurements, namely: Content 75% “Satisfied”, Accuracy 76% “Satisfied”, Ease Of Use 87% “Very Satisfied”, Format 69% “Satisfied”, Timeliness 67% “Satisfied”, so that the final result of the average index is 74.8%. It is hoped that it can recommend platform improvements, and be used for future research to support the development of AI-powered applications in a block-based environment.